PENGARUH UKURAN PERUSAHAN, FINANCIAL DISTRESS, RESIKO LITIGASI TERHADAP KONSERVATISME AKUNTANSI - Mega Andani; Netty Nurhayati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, The purpose of this research is to examine the effect of company size, financial distress, litigation risk on accounting conservatism in the food and beverage manufacturing sub-sector listed on the Indonesia Stock Exchange in 2016-2019. The population of this research used food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019 as many as 30 companies. The research sample used purposive sampling technique. The research sample used was 19 companies. The analysis technique uses multiple linear regression. The results of this research indicate that company size has an effect on accounting conservatism, financial distress has no effect on accounting conservatism, litigation risk has an effect on accounting conservatism in the manufacturing of the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2016-2019.